Removal of Company Directors in Malaysia: Section 128 of the Companies Act 1965 and Associated Case Law Revisited - Lingam, S.T; Rama, Sri (Journal of Malaysian and Comparative Law, 2009)
This article aims to revisit s 128 of the Companies Act 1965 and associated case law with the objective of assessing the strengths and weaknesses of the aforesaid Malaysian position on removal of directors and also to highlight what the writers consider to be areas of doubt and controversy.